2009
DOI: 10.1111/j.1399-302x.2009.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference with Aggregatibacter actinomycetemcomitans: colonization of epithelial cells under hydrodynamic conditions

Abstract: These data confirm the possibility of applying beneficial bacteria in periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…S. mitis has been described as a bacterium with an ecological control function in the oral cavity. Precisely, S. mitis could inhibit A. actinomycetemcomitans colonization [41][45]. Our results support this observation and associate the inhibitory effects of S. mitis to both the initial step as well as the ensuing multiplication ability of A. actinomycetemcomitans .…”
Section: Discussionsupporting
confidence: 85%
“…S. mitis has been described as a bacterium with an ecological control function in the oral cavity. Precisely, S. mitis could inhibit A. actinomycetemcomitans colonization [41][45]. Our results support this observation and associate the inhibitory effects of S. mitis to both the initial step as well as the ensuing multiplication ability of A. actinomycetemcomitans .…”
Section: Discussionsupporting
confidence: 85%
“…Using different cell lines (gingival, bronchial, pharyngeal, and intestinal epithelial mucosa), it has been shown that NF-B activation and IL-8 production were reduced after stimulation with flagellin from pathogens such as Yersinia enterolitica, Aggregatibacter actinomycetemcomitans, Pseudomonas aeruginosa, and Salmonella enterica subsp. enterica serovar Typhimurium (20,25,27,28). Although here we described anti-inflammatory properties of S. salivarius on stimulated IECs, we also showed that the immunomodulation properties of these strains were different on immunocompetent PBMCs.…”
Section: Discussionmentioning
confidence: 53%
“…The S. salivarius TOVE-R strain has been reported to be a successful antagonist of virulent streptococci involved in tooth decay or pharyngitis, such as Streptococcus mutans, Streptococcus sobrinus, and Streptococcus pyogenes (19), or pathogens involved in periodontitis (20,21). The inhibitory activity toward S. pyogenes and Streptococcus pneumoniae has been attributed to bacteriocin production (22)(23)(24).…”
mentioning
confidence: 99%
“…sanguinis may decrease the release of IL-8 by the epithelial cells stimulated with Fusobacterium nucleatum and A. actinomycetemcomitans [62][63][64].…”
Section: Probiotic Effect On Immune Responsesmentioning
confidence: 99%